Treating obesity - is diet enough? - Gligorijević, Jelena; Stevanović, Slavica; Stanković, Veroslava; Zuber, Andrijana; Avramović, Avramović (PONS - medicinski časopis, 2024)
Obesity is prevalent, complex chronic disease, which can lead to more than 200 diseases, including diabetes, cardiovascular and malignant diseases. Weight bias, stigmatization and discrimination are widespread and with serious consequences for people living with obesity. Approved methods for obesity treatment are: 1. Nutrition improvement; 2. Physical activity; 3. Psychotherapy; 4. Pharmacotherapy; and 5. Surgical therapy. Nutrition interventions and medical nutrition therapy are core treatment for obesity. Nutrition interventions that are safe, effective, nutritionally adequate, culturally acceptable and affordable for long-term adherence, should be considered for adults living with obesity. However, to date, no single best nutrition intervention has been shown to sustain weight loss long-term. Physical activity, psychotherapy, pharmacotherapy and surgical therapy can considerably improve results of treatment, but all together, treating of obesity is complex, expensive and with limited results. It has been suggested that primary prevention is the most cost-effective option for addressing obesity. Therefore, prevention of obesity and related health consequences should be a focus of every healthcare systems.